A novel contrast stain for the rapid diagnosis of pityriasis versicolor: A comparison of Chicago Sky Blue 6B stain, potassium hydroxide mount and culture - Nikita Lodha; Shital Amin Poojary (Wolters Kluwer Medknow Publications, 2015)
Background: The mycological study of pityriasis versicolor is usually done by potassium hydroxide (KOH) mount and culture. However, KOH mount lacks a color contrast and requires a trained eye to interpret, while culture is difficult to perform, time consuming and has low sensitivity. Chicago Sky Blue 6B (CSB) is a new contrast stain that highlights the fungal hyphae and spores, blue against a purplish background. Aims and Objectives: This study was done to compare the utility of a novel contrast stain (CSB stain) with KOH mount and culture. Materials and Methods: Skin scrapings from the lesions of 100 clinically diagnosed cases of P. versicolor were subjected to (1) KOH mount and CSB stain for direct microscopic examination and (2) culture using Sabouraud's dextrose agar. The statistical analysis of CSB stain and culture was done using KOH mount as the reference method, as it is the most commonly performed and practical diagnostic test available for P. versicolor. An interrater reliability analysis using the Cohen's Kappa statistic was performed to determine consistency (agreement) among the different modalities. Observations and Results: Direct microscopy with CSB stain, KOH mount and mycological culture showed positive results in 98 (98%), 92 (92%) and 56 (56%) patients, respectively. Using KOH mount as the reference method, CSB stain had a sensitivity of 100% which was significantly higher than culture (60.9%). Statistically significant fair agreement was found between CSB stain and KOH mount (94% with κ=0.38, P < 0.001). Negligible agreement was found between CSB stain and culture (66%, κ=0.199, P = 0.001) as well as between KOH mount and culture (64%, κ=0.051, P = 0.107). Conclusion: CSB staining of skin scrapings is the most sensitive method for the diagnosis of pityriasis versicolor. Due to the distinct contrast provided by CSB, it is easy to perform, rapid and qualitatively superior to KOH mount.